In-depth characterization of CD24highCD38high transitional human B cells reveals different regulatory profiles - Simon, Quentin; Pers, Jacques-Olivier; Cornec, Divi; Le Pottier, Laëtitia; Mageed, Rizgar A.; Hillion, Sophie (Journal of allergy and clinical immunology, 2016)
CD24highCD38high transitional B cells represent cells at a key stage in their developmental pathway. In addition, these B cells have been widely ascribed regulatory functions and involvement in the control of chronic inflammatory diseases. However, the phenotypic and functional overlap between these cells and regulatory B cells remains controversial. In this study we wanted to explore the regulatory properties of CD24highCD38high human B cells. We used multicolor flow cytometry in combination with bioinformatics and functional studies to show that CD24highCD38high B cells can be distinguished into multiple subsets with different regulatory functions. For the first time, the study reveals that human transitional B cells encompass not only transitional type 1 and type 2 B cells, as previously suggested, but also distinct anergic type 3 B cells, as well as IL-10–producing CD27+ transitional B cells. Interestingly, the latter 2 subsets differentially regulate CD4+ T-cell proliferation and polarization toward TH1 effector cells. Additional analyses reveal that the percentage of type 3 B cells is reduced and the frequency of CD27+ transitional B cells is increased in patients with autoimmune diseases compared with those in matched healthy subjects. This study provides evidence for the existence of different transitional B-cell subsets, each displaying unique phenotypic and regulatory functional profiles. Furthermore, the study indicates that altered distribution of transitional B-cell subsets highlights different regulatory defects in patients with different autoimmune diseases.